Perceiving the Principles of Politeness in Promoting Beauty Products by Instagram Influencers - Asrat, Nurul Astaina; Sunusi, Seny Luhriyani; Amin, Fatimah Hidayahni; Susanto, Ashabul Kahfi (Journal of Excellence in English Language Education, 2025)
This study aimed to identify, classify, and analyze the use of maxims related to the politeness principles found in the Instagram posts of influencers Tasya Farasya and Dilla Jaidi. The method used in this study is qualitative research. The technique of this study is observation and documents. Data were collected from Instagram posts in the form of comments from netizens. This study adopted Leech's (1983) theory. The results show that six maxims of politeness principle are implemented, they are Tact, Generosity, Approbation, Modesty, Agreement, and Sympathy maxims. This study implies the understanding of online etiquette and the significance of politeness strategies in social media communication especially in promoting beauty products, which increasingly plays a central role in contemporary social and cultural exchanges in the field of Pragmatics study.